2013
DOI: 10.1002/dev.21118
|View full text |Cite
|
Sign up to set email alerts
|

Grasping the world through words: From action to linguistic production of verbs in early childhood

Abstract: We investigated whether the bodily-mediated production of verbs emerges earlier than verb recognition and oral production during early language acquisition. Children (aged 18-22, 23-27, 28-32, and 33-37 months) viewed animated pictures representing actions related to transitive and intransitive verbs and were asked to (i) orally indicate the verb presented, (ii) recognize the target verb among other verbs, and (iii) perform the actions corresponding to the target verb enunciated by the experimenter. Children 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…As child development theories, embodied cognition theories, and several experimental studies suggest, the development of language and motor abilities are strongly interconnected (Levi, Colonnello, Giacchè , Piredda, & Sogos, 2013;Glenberg & Gallese, 2012;Iverson & Braddock, 2011;Fischer & Zwaan, 2008;Piaget & Inhelder, 1966/1969. For example, at 2 years, typically developing children are able to perform specific actions when asked, even if they are unable to verbally produce the words representing those actions (Levi et al, 2013); however, at 3 years, children with SLI enact-express through the body-fewer action-related words than do typically developing children (Levi et al, 2014). In addition, children with SLI are less able to perform several motor-related tasks than are their typically developing peers (Iverson & Braddock, 2011;Hill et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As child development theories, embodied cognition theories, and several experimental studies suggest, the development of language and motor abilities are strongly interconnected (Levi, Colonnello, Giacchè , Piredda, & Sogos, 2013;Glenberg & Gallese, 2012;Iverson & Braddock, 2011;Fischer & Zwaan, 2008;Piaget & Inhelder, 1966/1969. For example, at 2 years, typically developing children are able to perform specific actions when asked, even if they are unable to verbally produce the words representing those actions (Levi et al, 2013); however, at 3 years, children with SLI enact-express through the body-fewer action-related words than do typically developing children (Levi et al, 2014). In addition, children with SLI are less able to perform several motor-related tasks than are their typically developing peers (Iverson & Braddock, 2011;Hill et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Facial transformation from a neutral expression sends complex signals, which are converted into emotions [ 7 ]. The practical and clinical applications of automatic emotion recognition have been extensively tested and validated [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of facial expression involves dynamic and multimodal phenomena. The transformation of the face from a neutral expression sends complex signals, which are converted into emotions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the second year of life, early production of verbs is mediated by body actions. Specifically, between 22 and 24 months, typically developing children are able to enact verbs, though their ability to recognize them by pointing and to verbally produce them is not yet fully developed (Levi, Colonnello, Giacche `, Piredda, & Sogos, 2013). Further, as van Batenburg-Eddes et al (2013) have recently demonstrated in a longitudinal study, neuromotor functioning at 12 weeks of age is a good predictor of receptive language at 1.5 years.…”
mentioning
confidence: 97%
“…We observed 3-year-old children because, at this age, children have already acquired a large number of verbs, and this is the typical age for referral and diagnosis of SLI. As in early childhood the gap between the ability to enact and to recognize verbs disappears during the second year (Levi et al, 2013), we determined whether children who have SLI show a discrepancy between these abilities at an age when these abilities are typically aligned.…”
mentioning
confidence: 99%